2010
DOI: 10.1161/circresaha.109.207670
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1 Is Essential for In Vivo Angiogenesis in Zebrafish

Abstract: Key Words: TRPC1 Ⅲ VEGF Ⅲ ISV Ⅲ angiogenesis Ⅲ zebrafish T he vascular system of vertebrates consists of a stereotyped and highly branched network of arteries, veins, and capillaries. This network extends into every tissue of the body and is tailored to its local physiological function. [1][2][3] The development of vascular networks requires 2 successive processes, vasculogenesis and angiogenesis. 1,2 During vasculogenesis, mesoderm-derived hemangioblasts differentiate in situ into endothelial cells (ECs), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 49 publications
(52 reference statements)
4
71
0
Order By: Relevance
“…On EA.hy926 cells, TRPC6 knockdown slightly reduced tube formation, a marginal effect compared with the important effect of TRPC3, TRPC4, and TRPC5 knockdown. TRPC1 was shown to have a prominent role in angiogenesis in zebrafish (33), but in mammals, no further data reported a role of TRPC channels in tube formation (14).…”
Section: Discussionmentioning
confidence: 99%
“…On EA.hy926 cells, TRPC6 knockdown slightly reduced tube formation, a marginal effect compared with the important effect of TRPC3, TRPC4, and TRPC5 knockdown. TRPC1 was shown to have a prominent role in angiogenesis in zebrafish (33), but in mammals, no further data reported a role of TRPC channels in tube formation (14).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo time-lapse imaging revealed that the angiogenic defect was attributable to impairment of filopodia extension, migration, and proliferation of ISV tip cells. TRPC1 acts synergistically with VEGFA in controlling ISV growth, and appeared to be downstream to VEGFA in controlling angiogenesis (Yu et al, 2010). Recently a role for TRPC1 in hypoxia-induced VEGF expression in U87 glioma cells has been reported.…”
Section: Role Of Trpc and Trpv Channels In Cell Cycle Arrest And Cytomentioning
confidence: 99%
“…Studies in zebrafish, have demonstrated that the involvement of TRPCs channels in angiogenesis represents a reminiscent of the role of TRPC channels in axon guidance (Yu et al, 2010). Activation of TRPC1 seems to be essential for the angiogenesis in vivo.…”
Section: Role Of Trpc and Trpv Channels In Cell Cycle Arrest And Cytomentioning
confidence: 99%
“…Remarkably, TRPC1 is proangiogenic in vivo: knockdown of zebrafish TRPC1 by morpholinos caused severe angiogenic defects in intersegmental vessel sprouting, presumably owing to impaired filopodia extension during EC migration [62] (table 1 and figure 2). …”
Section: Transient Receptor Potential Proteins and Stim1-orai1 Complexmentioning
confidence: 99%
“…HMEC, human microvascular EC; HPAEC, human pulmonary artery EC; HUVEC, human umbilical vein EC; EA.hy926, EC line derived from HUVEC fused with human lung adenocarcinoma cell line A549; PAEC, porcine aortic endothelial cells; BTEC, tumour-derived EC from breast carcinoma; H5VEC, heart endothelioma (H5V) EC; MAEC, mouse aortic EC; EPC, endothelial progenitor cells; RCC-EPC, EPC isolated from renal carcinoma patients; Numbers in parenthesis indicate the respective reference number. EPC [30] HMEC [31] BTEC [32] RCC-EPC [29] HUVEC [33 -35] HUVEC [36] HUVEC [37] HUVEC [38] HUVEC [36,39] MAEC from KO mice [40] HMEC [41,42] EPC [43] survival and proliferation RCC-EPC [29] EPC [30] HMEC [31] HUVEC [44] PAEC [45] H5V EC [46] HUVEC [40] HUVEC, HMEC [41,55] EPC [43] permeability HMEC,HUVEC [56 -58] HPAEC [59] Frog mesenteric microvessels [60] H5V EC [46] HUVEC [61] in vivo angiogenesis zebrafish [62] CAM [44] collateral growth [45] HERG-1-Retinoblastoma [63] EAG1-Xenograft in SCID mice and human osteosarcoma [27,28] CAM [54] xenograft in nude mice [38] Rabbit cornea [64] human mammary carcinoma, glioblastoma [65,66] AQP1 KO mice and C57BL/ 6 mice …”
Section: Transient Receptor Potential Proteins and Stim1-orai1 Complexmentioning
confidence: 99%